New species of the Rhagovelia orientalis species group (Hemiptera: Heteroptera: Veliidae) - Zettel, Herbert; Laciny, Alice (Zootaxa, 2021)
Three new species of the Rhagovelia orientalis species group are described from the Philippines: R. sophiae sp.n. from Catanduanes, R. masbatensis sp.n. from Masbate and Ticao, and R. orientaliformis sp.n. from western Mindanao. The species group now contains 30 species; 24 are endemic to the Philippines.